PENERAPAN TEKNOLOGI PAYMENT GATEWAY (MIDTRANS) PADA E-COMMERCE CV KERINCI GRAFIKA: CodeIgniter, E-Commerce, Midtrans, MySQL, Payment Gateway - Pariyadi, Pariyadi; Gusrial, Rama; Puspitorini, Sukma (LP2M Universitas Nurdin Hamzah, 2025)
This study discusses the development of an E-Commerce system for CV Kerinci Grafika aimed at resolving issues related to manual payment processing and transaction verification that previously required considerable time. The system is integrated with the Midtrans Payment Gateway to ensure that transactions are processed automatically, securely, and efficiently. The application was developed using PHP with the CodeIgniter 3 framework and a MySQL database. The research methodology employed the Software Development Life Cycle (SDLC) waterfall model, consisting of requirement analysis, design, implementation, testing, and maintenance. The system requires input data such as products, customers, and user authentication through login and registration. The core processes include product management, shopping cart handling, order processing, and online payment transactions. The outputs generated include transaction invoices, purchase history, and payment reports. The implementation results show that the system successfully improves operational efficiency and accelerates the payment verification process at CV Kerinci Grafika.